KORELASI LATIHAN METODE DISRTRIBUTED PRACTICE DAN MASSED PRACTICE TERHADAP KEMAMPUAN LOMPAT JAUH TANPA AWALAN PADA SISWA KELAS XI SMA NEGERI 3 WONOGIRI - Guntur Ratih Prestifa Herdinata; Aristiyanto Aristiyanto; Noer Indah Aprianti (Sekolah Tinggi Pariwisata Mataram, 2023)
Introduction: in this study the issues that must be examined regarding; the correlation of the distributed practice and massed practice methods to the long jump ability without a start, and whether there is a correlation between the distributed practice and massed practice methods to the long jump ability without a start in Wonogiri 3 Public High School students. This study aims to determine the correlation of distributed practice and massed practice methods on the long jump ability without a start, and the differences in the correlation of the distributed practice and massed practice methods on the long jump ability without a start on the students of SMA Negeri 3 Wonogiri. Research Method: The independent variable in this study is the method of distributed practice and massed practice, while the dependent variable in this study is the long jump ability without a prefix. the method used is quantitative research with an experimental form. The population in this study were 30 sample students in this study using a total sampling of 30 students. Data collection techniques using measurement techniques. The data collection tool uses a long jump test without a prefix. The data analysis technique uses a different test technique or t-test with a significance level of 5%. Research Results: The results of data analysis carried out before being given treatment, obtained the value of t between the pre-test in group 1 and group 2 = 0.0352, while ttable = 1.699. It turns out that the obtained t < t in the table, which means the null hypothesis is accepted. Thus group 1 and group 2 before being given treatment in a balanced state. Between group 1 and group 2 depart from the starting point of the same leg muscle power ability. Which means if after being given treatment there is a difference, it is because of the difference in the treatment given. The conclusions from this study: 1) There is a correlation of the distributed practice method on the long jump ability without a start in Wonogiri 3 State Senior High School students, the correlation of training with the distributed practice method is the t count of 5.6127 with the t table of 2.151. 2) There is a correlation between the massed practice method of training on the ability to jump long without a start in Wonogiri 3 State Senior High School students, the effect of training using the distributed practice method is with a t count of 3.0893 with a t table of 2.151. 3) There is a difference in the correlation between distributed practice and massed practice methods on the ability to jump long without a start on students of SMA Negeri 3 Wonogiri. The difference in the correlation of training with the massed practice method and the distributed practice method is that the t count is 1.7600 with the t table 1.699. It turns out that the obtained t > t in the table, which means the null hypothesis is rejected. Suggestion: In general, it can be said that the distributed practice and massed practice methods are variables that influence the improvement of the long jump ability without a start for students of SMA Negeri 3 Wonogiri. The distributed practice method turns out to have a higher effect than mass practice. This means that a type of game is very influential on the success of increasing the long jump ability without a prefix. With the method of distributed practice and massed practice that is taught, from simple to complex methods, so that the ability to jump long without a start can be improved properly.